Sistem Pendukung Keputusan dalam Penentuan Mutasi Non Pegawai Menggunakan Metode Aras (Additive Ratio Assesment) (Studi Kasus :Samsat Medan Selatan) - Ainun Zariah; Edy Rahman Syahputra; Dedy Irwan (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
The One-Stop Manunggal Administration System (Samsat) in South Medan is one of the government agencies in charge of providing public services in the form of administrative documents and directly to the community. However, the system that runs at the company is still semi-computerized, especially in determining the transfer of non-employees (honorary) to permanent employees, so that the determination of non-employee transfer decisions is very difficult to determine. The process of assessing non-employee transfers is carried out manually by evaluating non-employee performance in terms of time discipline, absenteeism, length of work, work experience and the latest education from honorary so that the value obtained is less accurate and inefficient because errors often occur in determining the value of non-employees. . The non-employee transfer process is carried out based on subjective assessments, and direct non-employee transfers are carried out based on the daily life of non-employees. In non-employee mutations it is still not well coordinated, this is because non-employee mutations are carried out based on reports received from the head of the section. Thus, the process of making non-employee mutation reports takes quite a long time and the reports received are less accurate. The purpose of this research is to build a system to help predict the performance value of non-employee employees whether it is in accordance with the criteria and to build a decision support system that can assist the company's human resource management in the non-employee transfer process.